STATE-BUILDING OF INDIA AND PAKISTAN IN THE FIRST YEARS OF INDEPENDENCE: HISTORIOGRAPHY OF THE PROBLEM - L. A. Chereshneva (Гуманитарные и юридические исследования)
The article outlines brief characteristics of Russian and foreign historiography of the state-building history of India and Pakistan in the first years of their independence.